Cosmopolitan criminality in modern British literature - Morehead, Craig Res (2015)
Advances in cosmopolitan mobility, hybridity, and transnationalism during the modern age contributed to new criminal identity formations and classifications of crimes. This dissertation examines modern British fiction’s construction of cosmopolitan criminality at a time of increased awareness of the intensifying influences outlaws and foreigners had on English culture. Cosmopolitan criminals populated new genres of crime fiction such as Victorian slum literature, Edwardian and late-modernist thrillers, detective fiction, and anarcho-terrorist narratives. I demonstrate how this crime fiction shaped cultural, legislative, and public reactions to criminal outsiders and rendered new types of foreign and international crimes visible to an anxious British public. This study advances our understanding of how cosmopolitan criminality became an important literary subject for indicating symbolic and material threats of transnational modernization and tested legal and cultural standards of normalcy couched as Englishness. I recover the many iterations and uses of cosmopolitan criminality from the mid-Victorian to late-modernist periods in order to show that foreign crime was a central concern for modern British authors. Chapter one examines the cosmopolitan criminal’s emergence as an atavistic, foreign menace comprising a “criminal race” in Victorian slum literature, such as in Arthur Morrison’s A Child of the Jago. I read slum literature’s association of cosmopolitan features with criminality as a way English authors distinguished an honest, English working-poor under threat from degenerate cosmopolitan criminals in the slums. Chapter two focuses on cosmopolitan crimes carried out by anarchists and terrorists in late-Victorian and Edwardian crime narratives by Henry James, Robert Louis Stevenson, Joseph Conrad, and G. K. Chesterton. Against the legislative backdrop of new anti-Aliens Bills and a general suspicion of cosmopolitanism these authors satirize cosmopolitan criminals and crimes to critique anti-cosmopolitan fervor in England. Chapter three reads Graham Greene’s late-modernist thrillers of the 1930s as foregrounding poetic justice as an alternate means for thinking about social justice. Subverting classic thriller tropes, Greene dramatizes the social imbalances that thwart justice for the economically disadvantaged and protect the crimes of the social and economic elite